Transverse stability of free-trimmed fishing vessels - Valerio Mena, Lenin J.C. (2000)
A large part of the accidents with fishing boats are due to problems of transversal stability during the fishing task, in which the boat lists at large angles, and many times, failing to recover, capsizes. In the studies and expert reports carried out by the Insurers, the conclusion is generally reached that the vessel exceeded its stability limit. This stability limit in some cases may not have been evaluated correctly. This work discusses the efficiency of the transverse static stability calculation used in the design of ships and fishing vessels of the Peruvian fleet, based on the traditional stability cross curve diagrams that condition the trim of the vessel to remain unchanged. The calculations carried out by the traditional method are compared with others carried out using a free trim calculation method, based on the concept of hydrostatic balance of floating bodies. The calculation method with free trim is presented, including an illustrative case.